ECONOMIC AND PRACTICAL ASPECTS OF THE RETAIL PAYMENT SYSTEM OF COMMERCIAL BANKS - Nomozov Rovshan Ergashkulovich (American Journals, 2025)
This article analyzes the economic essence and theoretical foundations of the retail payment system in commercial banks. Retail payments, as a key component of financial transactions between individuals, businesses, and banks, play a crucial role in monetary circulation, financial stability, and improving the quality of banking services. The article explores core concepts, functions, and the role of the retail payment system in a market economy, along with theoretical models drawn from international experiences. The author also proposes recommendations for improving retail payment services within the banking system of Uzbekistan.
Keywords: banking, retail payments, payment system, money circulation, banking services.